The Relationship of Nutrition Knowledge, Eating Habits, Stress, and The Role of Parents on the Incidence of Overnutrition in Adolescent at Al-Azhar 1 Islamic High School Jakarta - Desiani Rizki Purwanigtyas; Devieka Rhama Dhanny; Anna Fitriani; Nazhif Gifari; Zia Mu'tazzah Shabah (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2023)
The incidence of overnutrition in adolescents is still high, which can be caused by rapid physical, cognitive, psychosocial, and behavioral changes affecting their nutritional status. This study aimed to determine the relationship between nutritional knowledge, eating habits, stress, and the role of parents in the incidence of overnutrition in adolescents at Al-Azhar 1 Islamic High School Jakarta. This study used a cross-sectional design and was conducted on 245 students of classes X and XI. Nutritional knowledge data were obtained by filling out questionnaires independently. Data on eating habits were obtained by filling out the Adolescent Food Habits Checklist (AFHC) questionnaire, stress data by the Perceived Stress Scale (PSS), and parental role data by the Family Health Climate for Nutrition (FHC-NU) and the Family Health Climate for Physical Activity (FHC-PA). The proportion of students with overnutrition is 20%, and obesity is 18.4%. The results showed a significant relationship between the incidence of overnutrition and eating habits (p=0.000) and stress levels (p=0.022). However, there was no significant relationship between the incidence of overnutrition and nutritional knowledge (p=0.437) and the role of parents (p=0.724). Therefore, adolescents need to pay attention to eating habits, control stress levels, consume healthy and nutritious food, and maintain a normal weight to prevent the risk of overnutrition.